ANALISIS FAKTOR RISIKO KANKER PAYUDARA DI RUMAH SAKIT UMUM PUSAT HAJI ADAM MALIK MEDAN - dede maysarah (Jurnal Maternitas Kebidanan, 2018)
In Indonesia, breast cancer is the second rank in women with the highest percentage of new case of breast cancer (after having been controlled by age) is 43.3% and the percentage of death (after having been controlled by age) is 12.9%. The objective of the research was to analyze the risk factors for breast cancer at RSUP Haji Adam Malik, Medan. The research used quantitative method with case control design which consisted of case group of 37 respondents who were affected by breast cancer and control group of 37 respondents who were not affected by breast cancer. Matching was performed on age (± 5 years). The data were analyzed by using univatriate analysis, bivatriate analysis with McNemar test, and multivatriate analysis with conditional logistic regression analysis at α = 0.05. The result of the research, using multivatriate analysis, showed that the risk factors which influenced the incidence of breast cancer were the parity of the history of breast cancer in family (p=<0.001, OR 17.061; 95%CI:4.161-69.504), the length of using hormonal contraception (p=0.043, OR 4.018; 95%CI:1.087-14.855), and obesity (p=0.026, OR 4.710; 95%CI:41.200-18.491). It is recommended that respondents who have the history of breast cancer in family avoid the risk factors which can be modified such as the use of hormonal contraception in the long run, obesity, and smoking so that they can be prevented from breast cancer.